(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Agriculture plays a vital role in the Indian economy, providing livelihood to a significant portion of the population and contributing substantially to national income and export earnings. Among agricultural commodities, turmeric holds a prominent position due to its wide applications in food, medicine, cosmetics, and industry. India is the largest producer and exporter of turmeric, contributing nearly 80 percent of global production. However, despite its strong production base, the sector faces challenges such as limited value addition, inadequate processing infrastructure, and fluctuating market prices, which affect farmers’ income and export competitiveness. In this context, the establishment of the National Turmeric Board (NTB) marks a significant institutional initiative aimed at strengthening the turmeric value chain. The present study examines the role of the National Turmeric Board in promoting value addition and enhancing export competitiveness in India. The study is based on secondary data collected from government reports, publications of the Spices Board of India, and relevant research articles for the period 2023–2025. Analytical tools such as percentage analysis and comparative analysis are used to interpret the data. The study identifies low value addition, inadequate infrastructure, and market inefficiencies as major challenges affecting the turmeric sector. The findings highlight that the NTB plays a crucial role in improving quality standards, supporting research and development, promoting value-added products, and facilitating better market linkages for farmers and exporters. The study concludes that with effective implementation of policies and infrastructure support, the National Turmeric Board can significantly enhance farmer income, strengthen India's position in the global spice market, and promote sustainable agricultural development.